2006
DOI: 10.1191/0748233706th250oa
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis induced in mice after subacute and subchronic V2O5 inhalation

Abstract: Reports about vanadium (V) inhalation toxicity on the hematopoietic system, specifically about coagulation are limited. Therefore, we decided to evaluate the effects of V with a complete blood count and morphologic analysis of platelets on blood smears. CD-1 male mice inhaled V2O5 0.02 M 1 h twice weekly over 12 weeks. Blood samples were obtained by direct heart puncture; Wright stained smears were used for platelet quantification. An increase in platelet count from the third week of exposure was observed, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
4
21
0
Order By: Relevance
“…Previous reports from our group noted that vanadium can affect other tissues as well, including the blood and nervous systems (Gonzalez-Villalva et al, 2006) (Avila-Costa et al, 2004). We also have reported that vanadium impairs the immune system, with changes induced in the morphology of the spleen and decreases in humoral immune responses (Piñon-Zarate et al, 2008).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous reports from our group noted that vanadium can affect other tissues as well, including the blood and nervous systems (Gonzalez-Villalva et al, 2006) (Avila-Costa et al, 2004). We also have reported that vanadium impairs the immune system, with changes induced in the morphology of the spleen and decreases in humoral immune responses (Piñon-Zarate et al, 2008).…”
Section: Introductionmentioning
confidence: 70%
“…We have previously reported that the immune system is compromised in a V-exposed mouse model; in those studies, morphological and functional changes were noted in spleens of mice exposed to V (Fortoul et al, 2002;Gonzalez-Villalva et al, 2006). Because of the critical participation of the spleen in immune responses/ system function, we wondered whether effects would also manifest in another key immune system organ, the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are slight differences between those studies probably related to species differences or method of administering the vanadium, the tendency is to suppress the immune response. We have previously shown that the chronic inhalation of V 2 O 5 in CD1 mice induces an increase in the number and size of platelets (Gonzalez-Villalva et al, 2006). We have also seen that these vanadium-treated mice show macroscopic splenic lesions that might lead to histologic and functional alterations.…”
Section: Introductionmentioning
confidence: 80%
“…Megakaryocytic proliferation may result in increased production of platelets and increased risk for thromboembolic events [48] . Megakaryocytes arise from pluripotent hematopoietic stem cells capable of differentiation into all of the cell lines that reside in the bone marrow and produce blood cells.…”
Section: Discussionmentioning
confidence: 99%